Double‐blinded randomized controlled trial to evaluate a multimedia surgical care tour in improving patient satisfaction and knowledge after functional endoscopic sinus surgery. Issue 3 (13th December 2018) - Ma, Yue; Zeiger, Josh; McKee, Sean; Yang, Anthony; Schaberg, Madeleine; Del‐Signore, Anthony; Govindaraj, Satish; Iloreta, Alfred
Abstract : Background: Current delivery of patient education is done during the clinic visit, where physicians or clinic staff have limited time for each patient. One potential solution is to provide a multimedia surgical care tour delivered to patients throughout the perioperative period. The purpose of the study is to evaluate the effectiveness of this surgical care tour in enhancing patient knowledge and satisfaction after functional endoscopic sinus surgery (FESS). Methods: A total of 121 patients were enrolled and a double‐blinded randomized controlled trial was initiated. Patients in the experimental group received 4 educational videos and automated reminders to take medications. The control group received a sham platform. Patients were randomized by MEDUMO software, and physicians, clinic staff, and patients were blinded. Patient satisfaction was measured by Consumer Assessment of Healthcare Providers and Systems (CAHPS) Surgical Care Survey Version 2.0. Patient knowledge was graded by the blinded surgeon and clinic staff. Fischer's exact test and 2‐tailed independent samples Student t test were used to compare the satisfaction and patient knowledge outcomes, respectively. Results: Patients in the experimental group were more likely to answer "Yes, definitely" to "Did these pictures drawings models or videos help you better understand your condition and its treatment?" (95.7% vs 74.1%, p = 0.011). The mean ± standard deviation clinic staff assessment of patient knowledge was 3.04 ± 1.05 in the control group and 3.68 ± 1.41 in the experimental group ( p = 0.043). Conclusion: A multimedia surgical care tour was developed and has promising effects on patient satisfaction and knowledge after FESS.